The failure and fracture modes of 35CrMnSi steel projectile with simulated charge penetrating rock at about 1000 m/s. (March 2019) - Sun, Qiran; Sun, Yuxin; Li, Ruiyu; Deng, Guoqiang; Hu, Jinsheng
Abstract: To reveal the projectile failure and fracture modes during high-velocity impact, projectiles made of 35CrMnSi with the same shape but different shell thickness are designed and then the experiments of penetrating high-strength rock target at about 1000 m/s are carried out. The experimental results indicate that all projectiles are completely fractured with petal shaped fragments produced and fail to effectively penetrate the rock target while only the target surface is comminuted. Besides the discussion on projectile material strength failure based on experimental results, projectile structure damage in the form of dynamic plastic buckling failure is also applied and gives a satisfactory explanation for the fracture pattern of petal shaped fragments with three-hinges structures employed. In addition, by taking the failure model of Mott stochastic distribution into account for the projectiles, numerical simulations are carried out to analyze the projectile fracture modes by Autodyn-3D with different discrete forms and exhibit high credibility. Furthermore, the influences of the filling and different impact conditions including velocities, angles of attack (AOA) and incidence angles on the projectile fracture modes are discussed. In general, the experimental results and the adopted numerical method with high credibility are able to reveal the effect of projectile structure damage on fracture modes and can be referred to further study on the projectile fracture during high-velocity penetration. Highlights: Penetration experiments into high-strength rock are first conducted. The projectile fracture mode in experiments present as petal shaped fragments. Projectile structure damage is applied to explain the projectile fracture mode. The fracture process of projectile is obtained by numerical simulations. Different influence factors on projectile fracture mode are discussed.